THE EFFECT OF LAMP TYPES ON THE GROWTH AND PRODUCTION OF LETTUCE GROWN IN AN INDOOR HYDROPHONIC SYSTEM - Restiani, Ag Reni (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The objective of this research was to evaluate responses of grand rapid lettuce (Lactuca sativa L.) grown in anindoor hydrophonic system(awick system) under the treatments of some different types of lighting. The researchwas conducted in April to June 2015. The treatment in this reearch consisted of a single factor (types of lighting)with five levels: Sun lighting (N0), 2 tubes of 18Watt fluorescent lamp (N1), 2 sets of 36Watt LED + 1 tube of 150Watt halogenlamp (N2), 2 setsof 36Watt LED+ 2 tubes of18Watt fluorescent lamp (N3), and 150Wattbulb (N4).Each treatment consisted of four plantswhichwere grown in a 60 cmx 60 cmx 120 cmgrowth chambermade ofplywood, except for sun light treated plantswhich were placed inamini greenhouse. Results showed that amongthe plants in the growth chambers, the best vegetative growthwas shown by the lettuce in the treatment of 2 setsof 36Watt LED + 2 tubes of 18Watt fluorescent lamp (N3), However; compared to those plants grown under thesun light, the lettuce inN3 still looked etiolation because light intensitywas not optimal yet.Keywords: Lamp types, lettuce plants, wick systemhydroponic